A 6-amino acid insertion/deletion polymorphism in the mucin domain of TIM-1 confers protections against HIV-1 infection (2017)
ABSTRAC: We investigated whether a 6-amino acid insertion/deletion polymorphism in the mucin domain of TIM-1 (T-cell immunoglobulin and mucin domain 1), modulates susceptibility to HIV-1 infection. The polymorphism was genotyped in three case/control cohorts of HIV-1 exposed seronegative individuals (HESN) and HIV-1 infected subjects from Italy, Peru, and Colombia; data from a Thai population were retrieved from the literature. Across all cohorts, homozygosity for the short TIM-1 allele was more common in HESNs than in HIV-1 infected subjects. A meta analysis of the four association analyses yielded a p value of 0.005. In vitro infection assays of CD4þ T lymphocytes indicated that homo zygosity for the short allele is associated with lower rate of HIV-1 replication. These results suggest that the deletion allele protects from HIV-1 infection with a recessive effect.